A Study on Patient Satisfaction and Prevalence of Complication on Surgical Extraction of Third Molar - Ahtesham Ahmad Qurishi; Amal Bajonaid; Maryam H. Mugri; Husham E. Homeida; Ogail Yousif Dawod; Haider Hussain Alhijji; Albaraa Abeid Dayili (Journal of Pharmacy and Bioallied Sciences)
Introduction: The surgical extraction of third molars is a common procedure often accompanied by various complications. This study evaluates patient satisfaction and the prevalence of complications to identify factors influencing postoperative outcomes. Methodology: A cross-sectional study was conducted with 62 patients who underwent third molar extraction. Data on demographics, complications, and patient satisfaction were collected through medical records and structured questionnaires. Complications were assessed at 1 week and 1 month post surgery, and satisfaction was measured using a 5-point Likert scale. Results: The most common complications were pain (32.3%) and swelling (24.2%). Despite these issues, patient satisfaction scores were high, with pain management, communication, recovery experience, and overall satisfaction averaging above 4.0 on a 5-point scale. Severe complications such as nerve injury (4.8%) and trismus (8.1%) were less frequent. Conclusion: While minor complications are prevalent, effective pain management and communication contribute to high patient satisfaction following third molar extractions. Continued efforts to minimize complications can further improve patient outcomes and satisfaction.